Relationship between toluene concentration and RQ toluene with neurotoxic - Tualeka, Abdul Rohim; Jalaludin, Juliana; Adriyani, Retno; Russeng, Syamsiar S.; Rahmawati, Pudji; Ahsan, Ahsan; Indri H., Susilowati; Rasmaliah; SuardiZurimi; Nendissa, M.Maria; Devilia, Laela Agrista (ASR Research Center, 2022)
Toluene is very dangerous for human health. Workers who use toluene as a solvent can be exposed to the risk of health problems such as dizziness, vertigo, eye irritation, skin irritation, respiratory problems, liver, kidney, and central nervous system disorders. This study aims to determine the relationship between concentration and characteristics of non-carcinogenic risk of toluene with neurotoxic effects in five industries in the Surabaya area. This is an observational study with a cross-sectional design conducted on five industries in Surabaya that uses toluene as a solvent in the production process, namely in industries in Osowilangun, Ketintang, Jemursari, Kalijudan, and AUP. The population in this study was a total of 90 workers exposed to toluene in the five industries. The research sample of 77 people was taken using the accidental sampling method. The variables studied in this study were toluene concentration, toluene RQ and neurotoxic effects. A total of 50 workers (65%) have unsafe RQ. A total of 48 (62.3%) workers had neurotoxic effects. There was no relationship between toluene concentration and RQ toluene with neurotoxic effects (p value> 0.05). The majority of workers (52%) are in locations with toluene concentrations below the threshold limit value; The majority of workers (65%) have 50 unsafe RQs, and A total of 48 workers (62.3%) had neurotoxic effects; Respondents exposed to toluene concentrations above the threshold are at risk of having a neurotoxic effect of 1.38 times greater than respondents exposed to toluene below the threshold, respondents with RQ values in the unsafe category are at risk of having a neurotoxic effect of 1.4 times greater than respondents with RQ values in the safe category. RQ of toluene is the primary determining neurotoxic.